Traditional authorities as development brokers in rural education: evidence from the PPTAP in Ghana. Issue 3 (3rd April 2022) - Abrefa Busia, Kwaku
ABSTRACT: Development brokerage has become a crucial and enduring phenomenon where local actors link their communities to the international development and aid system. Using the case of the World Bank-led Promoting Partnerships with Traditional Authorities Project (PPTAP) with the Asanteman Council in 2003, this study investigates the brokerage roles played by Traditional Authorities (TA) towards rural education. This study finds that the role of TAs was significant concerning improved time-bound projects, greater community participation and ownership, de-politicisation of projects, and accelerated land acquisition processes. However, issues of sustainability and gender remain critical concerns for the overall success of TAs as development brokers.